Three-dimensional nonlocal buckling of composite nanoplates with coated one-dimensional quasicrystal in an elastic medium. (1st March 2020) - Guo, Junhong; Sun, Tuoya; Pan, Ernian
Abstract: Based on the nonlocal theory, three-dimensional (3D) buckling of composite nanoplates with coated one-dimensional (1D) quasicrystal (QC) is analyzed. The nanoplate is embedded in an elastic medium and is under uniaxial or biaxial compression. All edges of the QC nanoplate are simply supported and its interaction with the surrounding medium is simulated by the Pasternak-type model. In terms of the extended displacement and traction vectors, the eigensystem is first derived from the basic equations of nonlocal QC materials. Then 3D analytical solutions of the critical buckling load under compression are derived by using the propagator matrix method and the continuity condition on the interfaces of the nanoplate. The influence of the thickness and length-to-width ratio of the nanoplate, Winkler stiffness and shear modulus of the elastic medium, coating thickness and nonlocal parameter on the critical buckling load is analyzed. For a sandwich nanoplate made of QC and soft metallic aluminium, our numerical results indicate that QC coatings could offer an interesting alternative to surface reinforcement of soft metallic materials in industrial applications. The present 3D buckling model could further serve as a benchmark for various thin-nanoplate theories and for numerical methods in multilayered QC nanoplate modeling with nonlocal effect.